Hickman's analog and RF circuits - Hickman, Ian
Hickman's latest guide is essential reading for anyone designing analog circuits. This book, along with the recent Analog Circuits Cookbook also available from Newnes, will enlighten, inform, interest and even amuse readers, and give them the ability to tackle analog and RF design problems with confidence. Based on articles published in Electronics World, this book covers such topics as RF amplifiers, oscillator design and behaviour, waveform analysis, optoelectronics, filters and op-amps, as well as offering intriguing insights in chapters such as Cautionary Tales for Circuit Designers, Circu.